Enhancing students’ global competence through international business study missions - CHONG, Mark (Institutional Knowledge at Singapore Management University, 2021)
Purpose This paper aims to share how an Asian university enhanced students’ global competence through international business study missions (BSMs). More specifically, it focuses on how the design of these BSMs enabled “deep” learning beyond industry tourism and how 21st-century competencies such as “global competence” can be acquired through participation in short-term, faculty-led study missions. Design/methodology/approach Using the case study approach, it critically analyzes the learning goals and objectives, design decisions, implementation details and learning outcomes underlying three BSMs led by three instructors from the same university to the USA (New York), Germany (Berlin and Stuttgart) and South Korea (Seoul). Findings The study shows that students gained global competencies related to specific fields of study such as the creative industries, urban sustainability and entrepreneurship. It shows how design choices such as destination, range of organizations, length of individual visits, range of pedagogical techniques, intensity of preparation and quality of management contribute to students’ acquisition of global competencies. Research limitations/implications This research presents a subset of case studies that may limit the generalization of the findings; the bias that results from an unrepresentative, opportunistic sample (selection bias); and lack of quantitative causality in a qualitative evaluation. Practical implications The course design described here provides practical information for designing study abroad “deep” learning goals, objectives and outcomes focusing on global competence. Originality/value The detailed case studies of three instructors from different disciplines to achieve the country’s education vision of globally competent students.